Penerapan Skrining Stunting Education Terhadap Kemampuan Orang Tua Balita di Rsia Siti Khadijah Kota Gorontalo - Modjo, Dewi; Indriyaningsih, Sofiyah Tri; Nai, Ramlawaty (Universitas Malahayati, 2023)
ABSTRACT Stunting is a condition where there is a lack of nutrient intake during the golden period, not caused by growth hormone disorders or caused by certain diseases. Parents play a role in the maturity of the growth and development of children and are important for the early development of a child by stimulating children's development from an early age. This study aims to analyze the application of stunting education screening to the abilities of parents of toddlers at RSIA Siti Khadijah, Gorontalo City. This research is a quantitative study using the One group pre-test and post-test design which provides treatment or intervention to research subjects and then the effect of the treatment is measured and analyzed. This sampling uses total sampling with a total of 6 samples.The results of the analysis of the ability of parents of toddlers before and after being given stunting screening education. From the results of statistical tests on the variable ability of parents of toddlers before being educated, the value is obtained with a difference in mean value of 1.33 and after being given stunting screening education is 2.00 with a standard deviation value before being given education is 0.516 and the standard deviation value after is 0.632. Keywords: Application, Education, Stunting, Parental Abilities ABSTRAK Stunting merupakan keadaan kondisi kurangnya asupan zat gizi pada masa periode emas, bukan disebabkan oleh kelainan hormon pertumbuhan maupun yang diakibatkan oleh penyakit tertentu. Orang tua berperan dalam kematangan pertumbuhan dan perkembangan anak dan penting untuk perkembangan awal seorang anak dengan melakukan stimulasi perkembangan anak sejak dini. Penelitian ini bertujuan untuk menganalisis penerapan skrining stunting education terhadap kemampuan orangtua balita Di RSIA Siti Khadijah Kota Gorontalo. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain One group pre-test and post-test design yang memberikan perlakuan atau intervensi pada subyek penelitian kemudian efek perlakuan tersebut diukur dan dianalisis. Pengambilan sampel ini menggunakan total sampling dengan jumlah 6 sampel. Hasil analisis Kemampuan orang tua balita sebelum dan sesudah diberikan edukasi skrining stunting Dari hasil uji statistik pada variabel Kemampuan Orang tua balita sebelum dilakukan edukasi di dapatkan nilai dengan perbedaan nilai mean adalah 1.33 dan setelah diberikan edukasi skrining stunting adalah 2.00 dengan nilai standar deviasi sebelum diberikan edukasi adalah 0.516 dan nilai standar deviasi setelah adalah 0.632. Kata Kunci: Penerapan, Education,Stunting, Kemampuan Orang Tua